NILAI-NILAI KETELADANAN GURU DALAM INTERAKSI PEMBENTUKAN KARAKTER ANAK (PAUD) - Umi Salamah; Rokhyanto Rokhyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2020)
Departing from the various realities as described above, the implementer of this service wishes to examine the importance of the exemplary educators in shaping the character of children. This dedication will begin with the basic concept of modeling, then end with the importance of modeling for the teacher in shaping the personalities (characters) of children towards independence. The role of parents is very important, especially to catch the concrete rather than the abstract. As a second parent, the teacher might find it easy to communicate his message verbally. However, children will find it difficult to understand the message if they see that their education does not provide an example of the message it conveys. Advances in technology also have an impact on children's behavior along with the progress of science and technology. This gives a very big impact on the behavior of students who increasingly leads to negative things. Children's behavior patterns tend to deviate from the corridors of noble morals. Based on the range of exemplary values ​​in the interaction of character building namely: efforts to ask for parental support, not getting bored giving directions, cooperation of all parties. The factors supporting the exemplary methods in PAUD, teachers, teaching materials, the local environment and schools, technological progress.